THE ROLE OF PEER FEEDBACK IN UNIVERSITY STUDENTS’ WRITING PERFORMANCE DURING AN ONLINE PEER ASSESSMENT ACTIVITY - Masrul, Masrul; Erliana, Santi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2024)
Although the benefits of online peer assessment and peer feedback on writing performance have been demonstrated, many learners might not recognize or benefit from specific change responses. This study investigated the correlation between online peer assessment and peer feedback on student writing performance. The correlation test was employed to analyze the data in this study. This study involved 145 undergraduate students (75 females and 70 males) from the State University of Malang, where the English course is mandatory for all students. This study revealed that online peer assessment and peer feedback on students' writing performance had a significant and strong relationship. On the other hand, the differences between the online peer assessment and peer feedback variables in each group were insignificant. Peer assessment and online peer feedback might have a close relationship; they can help pupils enhance their writing skills. However, there were no significant variations in each group's online peer assessment and peer feedback factors.